Functional and morphological effects of diazepam and midazolam on tumor vasculature in the 9L gliosarcoma brain tumor model using dynamic susceptibility contrast MRI: a comparative study - Yan N; Zheng Y; Yang C (Dove Medical Press, 2017)
Nuo Yan,1 Yuzhen Zheng,2 Cheng Yang1 1Second Department of Anesthesiology, The Affiliated Hospital to Logistics University of PAP, Tianjin, 2Department of Anesthesiology, Tianjin Huanhu Hospital, Tianjin, China Abstract: Antiangiogenic therapy attenuates tumor growth by reducing vascularization. Diazepam (DZP) and midazolam (MZL) have antiangiogenic properties in human umbilical vein endothelial cells. Thus, we investigated the antiangiogenic activity of DZP and MZL in the rat 9L gliosarcoma brain tumor model. The effect on tumor vasculature was evaluated using dynamic susceptibility contrast magnetic resonance imaging with gradient-echo (GE) and spin-echo (SE) to assess perfusion parameters, including cerebral blood volume (CBV), cerebral blood flow (CBF), mean transit time (MTT), and mean vessel diameter. The GE-normalized CBF (nCBF) in the tumors of untreated controls was significantly lower than that in normal brain tissue, whereas the CBV and MTT were higher. DZP- and MZL-treated rats had higher CBF and lower CBV and MTT values than did untreated controls. The tumor size decreased significantly to 33.5% in DZP-treated rats (P<0.001) and 22.5% in MZL-treated rats (P<0.01) relative to controls. The SE-normalized CBV was lower in DZP-treated (32.9%) and MZL-treated (10.6%) rats compared with controls. The mean vessel diameter decreased significantly by 32.5% in DPZ-treated and by 24.9% in MZL-treated rats compared with controls (P<0.01). The GE and SE nCBF values were higher in DZP-treated (49.9% and 40.1%, respectively) and MZL-treated (41.2% and 32.1%, respectively) rats than in controls. The GE- and SE-normalized MTTs were lower in DZP-treated (48.2% and 59.8%, respectively) and MZL-treated (40.5% and 51.2%, respectively) rats than in controls. Both DZP and MZL had antiangiogenic effects on tumor perfusion and vasculature; however, the antiangiogenic activity of DZP is more promising than that of MZL. Keywords: diazepam, midazolam, 9L gliosarcoma, antiangiogenic, DSC-MRI